Integrated ultrafiltration process for the recovery of bromelain from pineapple waste mixture. Issue 3 (24th October 2016) - Nor, M. Z. M.; Ramchandran, L.; Duke, M.; Vasiljevic, T.
Abstract: The two‐stage ultrafiltration (UF) process was recently successfully applied to purify bromelain from pineapple crude waste mixture (CWM); however, further process improvements were required. Effects of manipulating transmembrane pressure (TMP) and cross‐flow velocity ( ʋ ) on the flux profile, enzyme recovery and enzyme purity were investigated at TMP of 1.0, 1.5, or 2.0 bar and ʋ of 0.16, 0.24, or 0.30 m/s. High TMP and ʋ resulted in high flux in both UF stages. Performing the process at the highest TMP and ʋ of 2.0 bar and 0.30 m/s, respectively, yielded the highest enzyme recovery in UF stage 1 (76.9%), but the lowest purity fold in UF stage 2 (1.4‐fold). The effects were inverted at reduced TMP and ʋ conditions. For appropriate flux and enzyme separation effectiveness, the process should be conducted at 2.0 bar and 0.30 m/s in UF stage 1, and 1.5 bar and 0.24 m/s in UF stage 2. Practical applications: An efficient purification technique is needed for bromelain production in order to improve the quality of purified enzyme as well as to reduce the overall processing cost. Thus, a developed membrane‐based process has been further improved for bromelain purification in effort to establish process feasibility, practicality and effectiveness. In‐depth deliberation on the effect of selected processing conditions (TMP and ʋ ) on membrane performance and bromelain separation in a two‐stage UF process system has been presented in this work. It provides insight into the flux performance, fouling formation as well enzyme separation during the membrane process. Hence, the best processing conditions can be selected, which would bring to and even lower cost system suitable for large‐scale bromelain production.